2002
DOI: 10.1046/j.1365-2265.2002.01576.x
|View full text |Cite
|
Sign up to set email alerts
|

Submandibular salivary gland volume is increased in patients with acromegaly

Abstract: Acromegalic patients have an increased volume of submandibular salivary glands, independently of the activity of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…These alterations contribute to increasing the collapsibility of lateral/posterior hypopharyngeal walls on inspiration, which may then become invaginated into the laryngeal vestibule during sleep apneic episodes (274). Descriptions also exist of tongue hypertrophy causing fatal asphyxia (9), voluminous bilateral laryngocele (271), and increased volume of submandibular salivary glands (276). Remarkably, studies on static pharyngeal mechanics have identified the edge of the soft palate and the tongue base as the narrowest sites in the passive pharynx (277), whereas Morewood et al (278) documented obstruction of the upper airways in 23% of their patients due to the thickening of both true and false vocal cords.…”
Section: The Sleep Apnea Syndromementioning
confidence: 99%
“…These alterations contribute to increasing the collapsibility of lateral/posterior hypopharyngeal walls on inspiration, which may then become invaginated into the laryngeal vestibule during sleep apneic episodes (274). Descriptions also exist of tongue hypertrophy causing fatal asphyxia (9), voluminous bilateral laryngocele (271), and increased volume of submandibular salivary glands (276). Remarkably, studies on static pharyngeal mechanics have identified the edge of the soft palate and the tongue base as the narrowest sites in the passive pharynx (277), whereas Morewood et al (278) documented obstruction of the upper airways in 23% of their patients due to the thickening of both true and false vocal cords.…”
Section: The Sleep Apnea Syndromementioning
confidence: 99%
“…Clinically, not only dental components are modified by GH and IGF-1 excess but also soft tissue may be involved in facial changes due to acromegaly. In fact, it has been found that acromegalic patients commonly have enlarged submandibular glands (regardless of the activity of the disease) [31][32][33], though the parotid is rarely affected [34]. Glandular function is generally not compromised in these cases, and the pathophysiology related to these manifestations is not clear [34,35].…”
Section: Oral Manifestations and Maxillo-facial Featuresmentioning
confidence: 99%
“…High circulating growth hormone levels are also associated with salivary gland enlargement in patients which correlates with concomitant raised serum IGF-I concentrations. 141 In rodents several pharmacological agents, particularly sympathomimetic amines, have been shown to produce increases in salivary gland size following repeated dosing. 142 There is an intimate relationship of sympathomimetic amines with the control of the secretory process in salivary tissue.…”
Section: Atrophymentioning
confidence: 99%